Education and Ethics in the Life Sciences: Strengthening the Prohibition of Biological Weapons - Rappert, Brian (Practical Ethics and Public Policy Monograph, 2010)
At the start of the twenty-first century, warnings have been raised in some quarters about how - by intent or by mishap - advances in biotechnology and related fields could aid the spread of disease. Science academics, medical organisations, governments, security analysts, and others are among those that have sought to raise concern. Education and Ethics in the Life Sciences examines a variety of attempts to bring greater awareness to security concerns associated with the life sciences. It identifies lessons from practical initiatives across a wide range of national contexts as well as more general reflections about education and ethics. The eighteen contributors bring together perspectives from a diverse range of fields - including politics, virology, sociology, ethics, security studies, microbiology, and medicine - as well as their experiences in universities, think tanks and government. In offering their assessment about what must be done and by whom, each chapter addresses a host of challenging practical and conceptual questions. Education and Ethics in the Life Sciences will be of interest to those planning and undertaking training activities in other areas. In asking how education and ethics are being made to matter in an emerging area of social unease, it will also be of interest to those with more general concerns about professional conduct.